Strategi Penghimpunan Dana Melalui Produk Simpanan Syariah Di BMT UGT Nusantara Yosowilangun - Rusmini, Rusmini; Sari, Dewi Mayang; Salsabela, Zami; Munawir, Achmad; Annaafi'u, Dwi Nur (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to analyze the fund-raising strategies implemented through Shariabased savings products by BMT UGT Nusantara Yosowilangun. The research focuses on various types of Islamic savings products, such as savings and general deposits using Sharia contracts, as well as the strategies adopted by the BMT to mobilize community funds and assess their effectiveness in increasing both the number of members and the total amount of deposits. The study employs a qualitative descriptive approach, with data collected through interviews, field observations, and documentation. The findings reveal that BMT has implemented several fund-raising strategies, including promotional activities, a door-to-door service system, transaction digitalization, the application of mudharabah and wadiah contracts, and strengthening synergy within the Islamic financial ecosystem. These strategies have proven to be quite effective in increasing membership and savings volume. However, several challenges remain, such as low levels of Islamic financial literacy among the community and competition from conventional financial institutions. Based on these findings, the study recommends enhancing Sharia financial education, developing more innovative and adaptive savings products, and improving digital service quality to achieve more optimal fund mobilization.